Fundamentals of futures and options markets - Hull, John, 1946- 4 0 16; 5 (Upper Saddle River, N.J. : Pearson Prentice Hall)
This new edition presents a reader-friendly textbook with lots of numerical examples and accounts of real-life situations.
Includes bibliographical references and index.
System requirements (DerivaGem): Windows 2000 (SP4) and Windows XP (SP1, SP2
System requirements for accompanying disc: 133 MHz Pentium Processor; 64 MB RAM; Windows 2000 or later; Microsoft Excel 2000 or later; 800x600 display; 2x CD-ROM drive ;System requirements (DerivaGem): Windows 2000 (SP4) and Windows XP (SP1, SP2)
Keywords: 2 -- 0; 6; Problems, exercises, etc.;Problems, exercises, etc. -- Futures market.;Options (Finance).;Futures market;Options (Finance); 20; 2